World Health Organization Regional Assessments of the Risks of Poliovirus Outbreaks. Issue 4 (23rd March 2013) - Lowther, Sara A.; Roesel, Sigrun; O'Connor, Patrick; Landaverde, Mauricio; Oblapenko, George; Deshevoi, Sergei; Ajay, Goel; Buff, Ann; Safwat, Hala; Salla, Mbaye; Tangermann, Rudi; Khetsuriani, Nino; et al.
Abstract : While global polio eradication requires tremendous efforts in countries where wild polioviruses (WPVs) circulate, numerous outbreaks have occurred following WPV importation into previously polio‐free countries. Countries that have interrupted endemic WPV transmission should continue to conduct routine risk assessments and implement mitigation activities to maintain their polio‐free status as long as wild poliovirus circulates anywhere in the world. This article reviews the methods used by World Health Organization (WHO) regional offices to qualitatively assess risk of WPV outbreaks following an importation. We describe the strengths and weaknesses of various risk assessment approaches, and opportunities to harmonize approaches. These qualitative assessments broadly categorize risk as high, medium, or low using available national information related to susceptibility, the ability to rapidly detect WPV, and other population or program factors that influence transmission, which the regions characterize using polio vaccination coverage, surveillance data, and other indicators (e.g., sanitation), respectively. Data quality and adequacy represent a challenge in all regions. WHO regions differ with respect to the methods, processes, cut‐off values, and weighting used, which limits comparisons of risk assessment results among regions. Ongoing evaluation of indicators within regions and further harmonization of methods between regions are needed to effectively plan risk mitigation activities in a setting of finite resources for funding and continued WPV circulation.